934 Gliomas incidence in italy. (24th April 2018) - Modenese, Alberto; Korpinen, Leena; Gobba, Fabriziomaria
Abstract : Introduction: The International Agency for Research on Cancer has classified Radio Frequency in the Group 2B, 'possibly carcinogenic to humans', based on an association found between exposure related to mobile phones use and risk of gliomas and acoustic neuromas, even if this classification was discussed for some inconsistencies. Considering the large increase in mobile phone users from the '80 s, an increase in incidence of these tumours should be expected. The aim of this work is to follow the incidence of gliomas in Italy. Methods: The national incidence of central nervous system (CNS) cancers and that of gliomas from 2006 was obtained from the Italian Cancer Registries Result: Considering CNS cancers, in the period 1996–2009 the yearly age-standardised incidence per 1 00 000 has decreased from 10.8 to 9.8 in males, and from 8.0 to 7.0 in females. The incidence of gliomas, available for years 2006–2009 only, shows a slight increase from 5.7 to 6.3 in males, while is substantially stable (around 4) in females. Discussion and conclusion: Since the late '90 s, mobile phone use in Italy has largely increased: according to World Bank data, rose from 11.3 mobile phones per 100 Italians in 1996, to 107.7 in 2004 (exceeding the number of inhabitants), and 142.1 in 2015. If RF esposure related to mobile phones is associated with gliomas, considering a possible latency of 10–20 years an increase of the incidence of this tumours should be expected, at least from the second half of the 2000s Considering all CNS tumours, during the period 1996–2009 data show a decreasing trend in Italy. For glioma, currently available standardised incidence rates, covering only the period 2006–2009, suggest a slight increase, but limited to males. Data available at this moment do not adequately support any firm conclusion on the trends of these tumours in Italy.